Comportamento da lipólise durante o exercício e da taxa metabólica de repouso como respostas iniciais a um programa de treinamento aeróbio em indivíduos com sobrepeso e obesidade: um estudo controlado e randomizado - Ferreira, Ana Paula Urbano (2019)
Introduction: Interventions with physical training aimed at presented little expressive results and adaptive thermogenesis is pointed out as a mechanism that limits this weight loss. Several mechanisms are involved in this phenomenon, but still very little explored, including a minor lipolysis in response to the onset of an aerobic physical training program. Objective: analyze the behavior of metabolic rate and lipolysis during a standardized exercise session before and during the beginning of the aerobic physical training program of overweight and obese adult individuals. Methods: randomized controlled clinical trial. The study was performed with 15 subjects randomized into exercise group (n = 10) and control group (n = 05). All participants underwent initial tests of resting metabolic rate, ergospirometry, DXA and performed a standard exercise session (SES) lasting 40 minutes and intensity equivalent to the anaerobic threshold (AT). In this session, blood samples were taken at 20 min and 40 min for glycerol dosing and the submaximal oxygen consumption was measured from 5 to 15 min and from 30 to 40 min. A protocol of aerobic training duration of 04 weeks (2 weeks <LA and 2 weeks in LA) was performed. SPE was performed after two weeks of adaptation and two weeks of training. Results: the glycerol behavior was different after the intervention in the exercise group. From baseline to 20 minutes there was a reduction in glycerol levels (Δpre = 0.0031 vs Δpost = -0.0310), but without (Δpre = - 0.0510 vs Δpost = 0.01596, p = 0.218). This difference was statistically different from the control group. From 20 to 40 minutes there was a reduction in exercise group (Δpre =0.0160 vs Δpost = -0.00201), but also with no statistical difference in relation to the control (Δpre 0.03236 = vs Δpost = -0.01844, p = 0.147). Oxygen consumption, respiratory quotient and energy expenditure had similar behaviors between the groups during the experimental procedure at all moments evaluated (p> 0.05 for all comparisons). Conclusion: The use of aerobic physical training positively regulates lipolysis capacity in obese individuals, although it is not able to modify body capacity and resting metabolic rate, it is a great mobilization of glycerol.